2020
DOI: 10.3233/xst-200667
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central, peripheral, and weighted size-specific dose in CT

Abstract: The objective of this study is to determine X-ray dose distribution and the correlation between central, peripheral and weighted-centre peripheral doses for various phantom sizes and tube voltages in computed tomography (CT). We used phantoms developed in-house, with various water-equivalent diameters (Dw) from 8.5 up to 42.1 cm. The phantoms have one hole in the centre and four holes at the periphery. By using these five holes, it is possible to measure the size-specific central dose (Ds,c), peripheral dose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
(49 reference statements)
0
4
0
1
Order By: Relevance
“…However, the diameter of the head of every patient fluctuates along the z-axis, and an accurate estimate of organ dose should consider this fluctuation. The SSDE along the z-axis depends on D w in fixed tube current (FTC) and depends on both D w and tube current in tube current modulation (TCM) [27]. A previous study [28] reported estimated the TLD measurements were about 16% [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diameter of the head of every patient fluctuates along the z-axis, and an accurate estimate of organ dose should consider this fluctuation. The SSDE along the z-axis depends on D w in fixed tube current (FTC) and depends on both D w and tube current in tube current modulation (TCM) [27]. A previous study [28] reported estimated the TLD measurements were about 16% [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose distribution in the center of a 16 cm PMMA phantom was reported to be similar to the dose at the periphery [26]. In another study, Anam et al [27] explored various physical sizes of acrylic phantoms within a range of 8-32 cm and reported that D w within a range of 12-14 cm had a homogeneous dose distribution for both central and peripheral regions. Therefore, the SSDE may be useful for organ dose estimation within the head region without any consideration of fluctuations in the radial dose distribution.…”
mentioning
confidence: 97%
“…Para simplificar esta cuestión, hemos supuesto que CTDI ∝ D ∝ e −µd y utilizando la relación entre el CTDI periférico (CTDI p ) y el CTDI central (CTDI c ) como CTDI p CTDI c = k , descrita por Choirul et al, 8 hemos llegado a la siguiente expresión, en una primera aproximación, para el coeficiente de atenuación efectivo según el equipo utilizado:…”
Section: Coeficiente De Atenuación Lineal Efectivo µunclassified
“…The X-ray attenuation is a fundamental parameter effecting X-ray absorption and the dose absorbed by patient. The patient characteristics are generally represented by the water-equivalent diameter (D W ) [15,16] of the patient. Its value can be determined from patient images [7,17,18].…”
Section: Introduction mentioning
confidence: 99%